Ageing and the skill portfolio: Evidence from job based skill measures - Audra J. Bowlus; Hiroaki Mori; Chris Robinson (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2016)
The evolution of human capital over the life-cycle, especially during the accumulation phase, has been extensively studied within an optimal human capital investment framework. Given the ageing of the workforce, there is increasing interest in the human capital of older workers. The most recent research on wage patterns has adopted a new multidimensional skills/tasks approach. We argue that this approach is also well suited to the investigation of the evolution of the human capital of older workers. There is clear evidence that the typical concave Ben-Porath shape for a wage based single dimension human capital measure masks different shapes for the individual components in a multidimensional skill portfolio. Not all components evolve in the same way over the life-cycle. Some components of the skill vector are particularly sensitive to ageing effects for older workers, but this sensitivity is under-estimated using occupation level rather than individual level skill observations. The evidence suggests that workers can and do adjust their skill portfolios in various ways as they approach retirement and that the decline in skills is not purely driven by selection.
Keywords: 330; Ageing; Skills; Human Capital